Epidemic spreading in interconnected complex system - Ni, Shiliu. (2013)
Complex system is a newly introduced concept that only has been studied for around two decades. As nowadays systems tend to be more correlated than usual. More and more studies are focusing on the interconnected/interdependent networks.